2015
DOI: 10.1159/000441723
|View full text |Cite
|
Sign up to set email alerts
|

Negativity for Specific Autoantibodies in Patients with Type 1 Diabetes That Developed on a Background of Common Variable Immunodeficiency

Abstract: Common variable immunodeficiency (CVID) is a heterogeneous group of disorders characterized by disturbed antibody production and a dysregulated immune system. Aside from recurrent infections, the most common complications of CVID are autoimmune complications, particularly autoimmune cytopenias. To date, type 1 diabetes mellitus (T1D) in combination with CVID has only been described as an unusual complication in several reports, but the true incidence of T1D with CVID remains unknown. We describe 2 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Pituch‐Noworolska et al in 2013 evaluated autoantibodies in children with CVID and report that antibodies are produced despite impaired humoral immunity, but their level might be lower than immunocompetent individuals affected by autoimmunity. In another study, Milota et al described 2 patients with a combination of T1D and CVID with serious impairment of antibody production. Moreover, autoantibodies were not detected in these patients at the time of diagnosis or during the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Pituch‐Noworolska et al in 2013 evaluated autoantibodies in children with CVID and report that antibodies are produced despite impaired humoral immunity, but their level might be lower than immunocompetent individuals affected by autoimmunity. In another study, Milota et al described 2 patients with a combination of T1D and CVID with serious impairment of antibody production. Moreover, autoantibodies were not detected in these patients at the time of diagnosis or during the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent autoimmune disorder in patients with CVID is autoimmune cytopenia, by far the most common occurring variably in 4-20% (ITP develop in 6-14% and AIHA in 5-7%), but pernicious anemia (1-9%), RA (1-10%), IBD (6-10%), SLE, autoimmune thyroid disease, hepatitis, vitiligo, psoriasis, Sjögren syndrome, and now primary biliary cirrhosis as well as inflammatory relapsing polychondritis have also less frequently been reported [6,69,70,71,72]. It should be noted that autoimmune disorders may be the first or at the time the only clinical manifestation of CVID diagnosis [73,74]. Two separate studies showed that 54% [75] and 62% [76] of subjected CVID patients had the first episode of ITP or AIHA prior to the diagnosis.…”
Section: Autoimmunity In Padsmentioning
confidence: 99%
“…Correspondingly, both T1D and AIT may develop in the abscence of speci c autoantibodies. The autoantibody negative cases comprise 3.5-19% from all T1D patiens (22,23), moreover, several seronegative T1D patients were also desribed amongst the CVID patients (10). Autoantibody negative AIT represents approximately 5% of all patients with AIT (24).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the markedly impaired antibody production, diseases hallmarked by the presence of autoantibodies, such as Autoimmune hemolytic anemia (AIHA) or Immune thrombocytopenic purpura (ITP), are amongst the most commonly diagnosed autoimmune complications in CVID patients, found in up to 38.9% of patients (7,8). An increased prevalence of other autoimmune diseases associated with the tissue speci c autoantibodies in comparison to general population was also reported, such as Autoimmune thyroiditis (AIT) or Type 1 diabetes (T1D) revealed in 0.8-8.7%, and 0.8-7.1% of CVID patients respectively (7,9,10). The mainstay of CVID management is a regular, long-term immunoglobulin replacement therapy (IRT).…”
Section: Introductionmentioning
confidence: 99%